2016
DOI: 10.1073/pnas.1604994113
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the role of mobility, behavior, and time scales in the spread of diseases

Abstract: The dynamics, control, and evolution of communicable and vectorborne diseases are intimately connected to the joint dynamics of epidemiological, behavioral, and mobility processes that operate across multiple spatial, temporal, and organizational scales. The identification of a theoretical explanatory framework that accounts for the pattern regularity exhibited by a large number of host-parasite systems, including those sustained by host-vector epidemiological dynamics, is but one of the challenges facing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 88 publications
(93 reference statements)
1
70
0
Order By: Relevance
“…It becomes irregular as the probability (ϕ) increases. In the model of Watts and Strogatz [14], the rewired short-cuts made the network composed of local clusters, whereas that of Newman and Watts [21] is a single local cluster.…”
Section: Description Of the Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…It becomes irregular as the probability (ϕ) increases. In the model of Watts and Strogatz [14], the rewired short-cuts made the network composed of local clusters, whereas that of Newman and Watts [21] is a single local cluster.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…Small World Network and Scale Free models have been used extensively to study human disease and other spreads (computer virus, rumor, etc.) [15][16][17][18][19][20][21][22][23][24]. Zekri and Clerc found that infection grows exponentially [25] above the percolation threshold [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus of several papers in this issue was predictive modeling, particularly how the interrelated dynamics of disease transmission and human behavior influence the ecology, evolution, and control of infectious diseases (29) across spatial, temporal, and organizational scales. Using a model of intrapatch disease spread and interpatch mobility, Castillo-Chavez et al (33) illustrate the limitations of existing theoretical frameworks with respect to modeling such complex adaptive systems. The authors call for the formulation of improved theoretical frameworks that can encompass such processes and disentangle the role of epidemiological and socio-economic forces.…”
Section: Human-environmental Healthmentioning
confidence: 99%
“…We define a sink to be a community where transmission is not self-sustaining [16]; in this community, ℛ " < 1. To model mobility/travel, we use a generalized Lagrangian approach proposed by Castillo-Chavez and colleagues [17][18][19]. This modeling approach allows individuals to remain identifiable as residents of their home community when they are in other communities.…”
Section: Introductionmentioning
confidence: 99%